Partial analogue‐assisted digital low dropout regulator with transient body‐drive and 2.5× FOM improvement. Issue 5 (1st March 2018) - Huang, Mo; Lu, Yan; Lu, Xing
Abstract : A partial analogue‐assisted (AA) digital low dropout regulator (D‐LDO) with also a transient body‐drive (BD) technique is proposed. The body of the power switches can be driven by the V OUT transient spike that is high‐pass coupled from the D‐LDO output when a load step occurs, for a temporary threshold voltage change. The BD technique thereby manages to provide more than 10% momentary output current. In addition, since the effectiveness of the AA loop is proportional to the ratio of the coupling capacitance and the parasitic capacitance, here, only about 1/5 of the most significant bit of the power switches are connected to the AA and BD networks. Therefore, the coupling capacitors are much reduced, comparing to the previous work. A simulated 100 mV undershoot is obtained under a 2‐to‐12 mA load step within 1 ns edge time, using only 40 pF total capacitor. A 0.09 ps figure‐of‐merit (FOM) of speed is thereby achieved, which is at least 2.5× better than state‐of‐the‐art works.